The Role of Amygdala in Self-Conscious Emotions in a Patient With Acquired Bilateral Damage - Piretti, Luca; Pappaianni, Edoardo; Lunardelli, Alberta; Zorzenon, Irene; Ukmar, Maja; Pesavento, Valentina; Rumiati, Raffaella Ida; Job, Remo; Grecucci, Alessandro (Frontiers in Neuroscience, 2020)
Shame plays a fundamental role in the regulation of our social behaviour. One intriguing question is whether amygdala might play a role in in processing this emotion. In the present single-case study, we tested a patient with acquired damage of bilateral amygdalae and surrounding areas as well as healthy controls on shame processing and other social cognitive tasks. Results revealed that patient’s subjective experience of shame, but not of guilt, was more reduced than in controls, only in when social standards were violated, while it was not different than controls in case of moral violations. The impairment in discriminating between normal social situations and violations also emerged. Taken together, these findings suggest that the role of mygdale in processing shame might reflect its relevance in resolving ambiguity and uncertainty, in order to correctly detect social violations and to generate shame feelings.